Characterizing Provenance of the Late Wisconsinan Rainy Lobe Using Fine-Fraction Geochemistry and Detrital Zircon Geochronology - Hinkemeyer, Audray (2023)
University of Minnesota M.S. thesis. 2023. Major: Geological Sciences. Advisor: Howard Mooers. 1 computer file (PDF); vii, 72 pages. Till of the Late Wisconsin Rainy lobe, which emanated from the Labradoran sector of the Laurentide ice sheet (LIS), is exposed at the surface from SW Minnesota to the extreme NE part of the State. The Rainy lobe advanced to its maximum limit in southwestern Minnesota well prior to the Last Glacial Maximum (ca. 27-30 ka BP) and retreated into Ontario by 17.9 ka BP. This till exhibits dramatic spatial and temporal changes in provenance from the Hewitt till of SW Minnesota to the Independence till in the NE. Two models have been proposed to explain the lithological differences (particularly carbonate) in Rainy Lobe tills. Goldstein (1989) postulated that the downglacier increase in carbonate in the Hewitt till was the result of progressive incorporation, by regelation or deformation, of older underlying till that was rich in carbonate. Larson (2008) concluded that the changes in sedimentology and landforms record systematic changes in provenance related to changing basal boundary conditions in the interior of the LIS. Early in this phase of glaciation, the sediments reflect long-distance transport from Hudson Bay, and later phases reflect increased proportions of felsic shield lithologies and Duluth Complex rocks with a corresponding decrease in carbonate. These two models of Rainy lobe till sedimentology are evaluated using mixing models, till matrix geochemistry, and detrital zircon geochronology. The multicomponent mixing model is developed to examine sedimentological variability by incorporation of older, underlying tills (e.g. Goldstein, 1989). The mixing model shows that the Hewitt till does not lie on the mixing curve, suggesting that mixing is not a viable model for the origin of the sedimentary variability in the Hewitt till. To evaluate the model of Larson (2008), which implies long vs. short transport distances, twenty-eight samples collected along a transect from SW to ...